2019
DOI: 10.1016/j.cgh.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use Is Associated With Improved Outcomes of Patients With Primary Sclerosing Cholangitis

Abstract: BACKGROUND & AIMS: There is increasing evidence that statins can benefit patients with chronic liver diseases, but their effects have not been studied in patients with primary sclerosing cholangitis (PSC). We performed a nationwide study in Sweden to determine the effects of exposure to drugs, including statins, in patients with PSC. METHODS: We studied a population-based cohort of patients in Sweden with PSC and concomitant ulcerative colitis or Crohn's disease from 2005 through 2014 (n [ 2914), followed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…Recently, the effect of statins on PSC was evaluated in a nationwide observational study in Sweden 1 13. The study included all patients diagnosed in Sweden with PSC and concomitant UC or Crohn’s disease from 2005 through 2014.…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the effect of statins on PSC was evaluated in a nationwide observational study in Sweden 1 13. The study included all patients diagnosed in Sweden with PSC and concomitant UC or Crohn’s disease from 2005 through 2014.…”
Section: Human Studiesmentioning
confidence: 99%
“…These include reduction in portal pressure, improved liver sinusoidal endothelial and hepatic microvascular dysfunction, decreased fibrogenesis, protection against ischaemia/reperfusion injury, safe prolongation of ex vivo liver graft preservation, reduced sensitivity to endotoxin-mediated liver damage, protection from acute-on-chronic liver failure (ACLF), prevention of liver injury following hypovolaemic shock and preventing/delaying progression of cirrhosis of any aetiology 7–12. Moreover, statins have been shown to have potential beneficial effects in the progression of other liver diseases, such as chronic sclerosing cholangitis and in preventing hepatocellular carcinoma (HCC) 13–15. Because of these many theoretically favourable effects, statins have evolved from being considered a risk to kind of wonder drugs for patients with chronic liver disease (CLD) 2.…”
Section: Introductionmentioning
confidence: 99%
“…Example for ‘yes’: ‘Additional limitations caused by the lack of clinical data are residual confounding from for example alcohol abuse, smoking, diabetes or obesity’ 20 …”
Section: Methodsmentioning
confidence: 99%
“…Existing data are limited to case reports and a prospective case series (n = 15, median 41 months of treatment) [158], and although improvement in ALP (mean DALP -557 [-55.8%]; ALP normalized in 5/15 patients) and histology (6/10, 2/10 and 2/10 showed improved, stable or worsened histology, respectively) was reported in this series, there were no convincing data of effect on clinical outcomes. Of note, a Swedish population based registry study have suggested an impact from azathioprine (and statins) on clinical outcomes in PSC [159], so further and more targeted assessments to this end may still be considered.…”
Section: Azathioprine Ciclosporin Tacrolimus Methotrexate and Mycmentioning
confidence: 99%